BUKU PENUNTUN PRAKTIKUM JARINGAN HEWAN MENGGUNAKAN VIRTUAL LABORATORY - Viola Vinca Valisa; Evi Suryawati; Arnentis Arnentis (Biogenesis, 2021)
The most problem occurs in the praticum in the real laboratory, so it's not going well. It can affect the depth of concepts, principles, laws and theories that must be understood by the biology teacher candidates. One of the alternatives that can be done is practicum to use a virtual laboratory. The purpose of research is to develop a practical guidebook for animal tissue materials in practicum activities using virtual laboratories for teacher candidates. This research was conducted at the Laboratory of PMIPA FKIP Riau University in December 2020–May 2021. It used a Research and Development (R&D) approach with ADDIE model. The instruments used are validation expert and response questionnaires. The results showed that the guide books is good quality and suitable to be used as independent learning resources to increase content knowledge for teacher candidates.